The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.24034/jiaku.v1i1.4996
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh PDRB Per Kapita Dan Jumlah Tenaga Kerja Terhadap Jumlah Pendapatan Pajak Daerah Provinsi Di Indonesia

Abstract: The purpose of this study is to analyze the effect of GRDP per capita and the labor number on the province tax revenue. Regional tax revenues for each province have different figures. It is suspected that GRDP per capita and number of labor affect local tax revenues. To answer the research hypothesis, multiple linear regression analysis was used. The data used in the study were sourced from the Badan Pusat Statistik in 2020. The dependent variable in this study is local tax revenue, while the independent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
0
0
4
Order By: Relevance
“…Based on the Shapiro-Wilk test results, the test statistic value was 0.98, and the p-value was 0.15. The p-value obtained is more significant than 0.05, so it can be concluded that the errors have a multivariate normal distribution (Susila & Pradhani, 2022) .…”
Section: Var Assumption Checkmentioning
confidence: 78%
“…Based on the Shapiro-Wilk test results, the test statistic value was 0.98, and the p-value was 0.15. The p-value obtained is more significant than 0.05, so it can be concluded that the errors have a multivariate normal distribution (Susila & Pradhani, 2022) .…”
Section: Var Assumption Checkmentioning
confidence: 78%
“…Untuk mengetahui pengaruh dari tujuan penelitian ini maka digunakan uji dari output boostrapping Susila, 2022). Variabel dikatakan berpengaruh signifikan apabila nilai p-value kurang dari 0,05 (Susila & Pradhani, 2022).…”
Section: Metode Penelitianunclassified
“…Pertumbuhan ekonomi adalah indikator keberhasilan pembangunan ekonomi berkelanjutan dari suatu daerah. Pengukuran pertumbuhan ekonomi dapat dilihat melalui Produk Domestik Regional Bruto (PDRB) daerah tersebut (Susila & Pradhani, 2022). Laju pertumbuhan ekonomi provinsi Jawa Timur dari 2017-2021 menurut data dari Badan Pusat Statistik (BPS) bisa dilihat di Tabel 1.…”
Section: Pendahuluan *unclassified